3D numerical modeling for thermo-mechanical behavior of additively manufactured titanium alloy parts with process-induced defects. (1st August 2023) - Li, Zhi-Jian; Xiao, Zhi-Heng; Zhang, Hai-Liang; Dai, Hong-Liang; Luo, Wei-Feng; Huang, Zheng-Wei
Highlights: Thermo-mechanical modeling of SLM-printed titanium alloy parts with process-induced defects is proposed. Temperature, residual stress and displacement fields of SLM-printed titanium alloy parts with defects are predicted. Effect of process parameters and defect on thermo-mechanical behaviors of SLM-printed titanium alloy parts is analyzed. Abstract: The defects due to the rapid heating and cooling in powder bed fusion affect significantly the mechanical properties of additively manufactured as-built parts. However, the effect of process-induced defects on the thermo-mechanical behaviors of as-built parts is still unclear. In this paper, considering the process-induced interfacial lack of fusion (LoF) and pores, we developed a coupled thermo-mechanical model of titanium alloy parts in the powder bed fusion process. The equivalent temperature-dependent thermal properties of the parts with defects are calculated based on mixture theory. The three-dimensional thermal, mechanical, and displacement fields are predicted based on the differential quadrature method (DQM). The accuracy of the proposed model is verified by the comparison with the predictions and experimental data in the references. The effect of crucial parameters on the thermo-mechanical responses of as-built parts is analyzed, including energy densities, scan patterns, preheating temperature, LoF dimension, porosity, and powder layer thickness. The predicted results show that the process and geometry parameters play a vital role in the temperature distribution, residual stress buildup, and deformation of the printed parts. In addition, the LoF defect triggers the stress jump at the interface of the defect/powder bed and powder bed/substrate. The predicted results can be beneficial to provide a guideline for the design and additive manufacturing of titanium alloys.